KEPEMIMPINAN TRANSFORMASIONAL DAN KINERJA PEGAWAI DI LEMBAGA PENDIDIKAN - Risa Sofiati; Ruswan Ruswan; Fatah Syukur (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the implementation of transformational leadership in fostering work engagement and improving employee performance in educational institutions. The phenomena examined stem from low employee work engagement, weak organizational communication, and suboptimal leadership in enhancing employee productivity and work effectiveness. This study employs a qualitative approach using a case study design to deeply understand the experiences, interactions, and meanings that emerge within the educational organizational environment. The research subjects include the head of the institution, teachers, administrative staff, and employees. Data collection techniques include interviews, observations, and documentation. Data validity was achieved through triangulation of sources and methods, while data analysis utilized the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that transformational leadership plays a crucial role in fostering employee work engagement through inspirational communication, work motivation, exemplary behavior, and a humanistic interpersonal approach. Employee work engagement is reflected in increased loyalty, discipline, responsibility, cooperation, and work productivity within the organization. Furthermore, a supportive organizational culture and harmonious social relationships between leaders and employees are key factors in enhancing the effectiveness of educational institutions.